2020
DOI: 10.3390/biom10060829
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of Apolipoprotein J-Derived Mimetic Peptide d-[113–122]apoJ Improves LDL and HDL Function and Prevents Atherosclerosis in LDLR-KO Mice

Abstract: Mimetic peptides are potential therapeutic agents for atherosclerosis. d-[113–122]apolipoprotein (apo) J (d-[113–122]apoJ) is a 10-residue peptide that is predicted to form a class G* amphipathic helix 6 from apoJ; it shows anti-inflammatory and anti-atherogenic properties. In the present study, we analyzed the effect of d-[113–122]apoJ in low-density lipoprotein receptor knockout mice(LDLR-KO) on the development of atherosclerosis and lipoprotein function. Fifteen-week-old female LDLR-KO mice fed an atherogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Indeed, this ratio has been reported to be significantly higher in ICR mice with HF diet–induced obesity than in control mice [ 35 ]. This is in accordance with our results, which showed that the total cholesterol/HDL-cholesterol ratio in the C-HF group was significantly higher than in the C-C group, while the ratios were similar in the Q-HF and C-C groups ( Figure 4 d), in which levels agree with the published values [ 36 , 37 ]. These results clearly indicate the possibility that maternal quercetin consumption may protect the next generation from disruption of cholesterol metabolism by consumption of a HF-diet, even though total cholesterol itself will increase.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, this ratio has been reported to be significantly higher in ICR mice with HF diet–induced obesity than in control mice [ 35 ]. This is in accordance with our results, which showed that the total cholesterol/HDL-cholesterol ratio in the C-HF group was significantly higher than in the C-C group, while the ratios were similar in the Q-HF and C-C groups ( Figure 4 d), in which levels agree with the published values [ 36 , 37 ]. These results clearly indicate the possibility that maternal quercetin consumption may protect the next generation from disruption of cholesterol metabolism by consumption of a HF-diet, even though total cholesterol itself will increase.…”
Section: Discussionsupporting
confidence: 93%
“…(Sigma Diagnostics, Livonia, MI, USA) with a final concentration of 50 mU/mL in the presence of 2 mM CaCl 2 and 2 mM MgCl 2 . Size-exclusion chromatography was performed for monitoring aggregation using a Superose 6 Increase 5/150 GL column in an AKTA-FPLC system (GE Healthcare), as described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the 4F peptide has been shown to reduce experimental murine atherosclerosis, especially when applied during the early stages of atherosclerosis [ 106 , 107 , 108 ]. Recently, Rivas-Urbina et al showed in LDL receptor-deficient mice that a 10-residue peptide from apoJ (clusterin) inhibits LDL aggregation by binding to modified LDL particles and that it also reduces atherosclerosis [ 109 , 110 ]. Thus, the LDL surface lipid monolayer-stabilizing effect of amphipathic peptides appears not to depend on the amino acid structure of the peptide, but rather on its ability to bind to the surface lipid monolayer.…”
Section: Attempts To Reduce the Aggregation Susceptibility Of Ldl Particles—from Molecular Understanding To Studies In Animal Models And mentioning
confidence: 99%